The Use of Phet Interactive Simulation Software in Physics Learning - Feby Liswar; Abna Hidayati; Rayendra Rayendra; Fetri Yeni (Jurnal Penelitian Pendidikan IPA, 2023)
Physics learning is a discipline that requires in-depth understanding and a strong grasp of concepts. The use of technology in physics learning has become very essential, such as in the use of PhET interactive simulation software. This article aims to explore literature studies regarding the use of PhET software in the context of physics learning and its positive impact on students' abilities. The literature review method was carried out by searching for articles and journals related to the use of PhET in physics learning. The study results show that the use of PhET in physics learning can increase students' understanding of physics concepts and motivate them to study physics. Strategies for using PhET in physics learning include using it as a tool in explaining physics concepts, creating virtual experiments by students, and preparing virtual experiment reports. This article is an effective and efficient alternative for increasing students' understanding of PhET in physics learning